A tail of two phages: genomic and functional analysis of Listeria monocytogenes phages vB_LmoS_188 and vB_LmoS_293 reveal the receptor-binding proteins involved in host specificity - Casey, Aidan; Jordan, Kieran; Neve, Horst; Coffey, Aidan; McAuliffe, Olivia (Frontiers in Microbiology, 2015)
The physical characteristics of bacteriophages establish them as viable candidates for downstream development of pathogen detection assays and biocontrol measures. To utilize phages for such purposes, a detailed knowledge of their host interaction mechanisms is a prerequisite. There is currently a wealth of knowledge available concerning Gram-negative phage-host interaction, but little by comparison for Gram-positive phages and Listeria phages in particular. In this research, the lytic spectrum of two recently isolated Listeria monocytogenes phages (vB_LmoS_188 and vB_LmoS_293) was determined, and the genomic basis for their observed serotype 4b/4e host-specificity was investigated using comparative genomics. The late tail genes of these phages were identified to be highly conserved when compared to other serovar 4-specific Listeria phages. Spontaneous mutants of each of these phages with broadened host specificities were generated. Their late tail gene sequences were compared with their wild-type counterparts resulting in the putative identification of the products of ORF 19 of vB_LmoS_188 and ORF 20 of vB_LmoS_293 as the receptor binding proteins of these phages. The research findings also indicate that conserved baseplate architectures and host interaction mechanisms exist for Listeria siphoviruses with differing host-specificities, and further contribute to the current knowledge of phage-host interactions with regard to Listeria phages.